The Organization's capabilities towards adopting TQM and its impact on the quality of services by applying to the Beshah Electricity Company - Al-Saied, Abdul Rahim Abbas Mousi Qasam (Journal of Economic, Administrative and Legal Sciences, 2017)
The research aims at measuring the effect of worker’s capacity to adopt the comprehensive quality administration. It was applied on sample from the administration of electricity of Bisha. The descriptive analytical method is used. A questionnaire is used for primary data collection. Statistical calculation are used, the mean, standard deviation, Alfa Cronbach, factor analysis, Pearson correlation, and the analysis of falling. The findings showed that the quality of services affects the abilities of workers when adopting the administration of the comprehensive quality. There is a significant statistical relation between the quality of services and the capacity of the workers.
Keywords: The capacity of the Organization; total quality management; quality of service